A multi-level pore beta molecular sieve material and a preparation method thereof

By introducing inorganic salts as mesoporous initiators into an extremely low water volume system and utilizing high-viscosity gels to generate mesopores, the problems of waste liquid discharge and raw material loss in the synthesis of hierarchical Beta molecular sieves were solved, achieving efficient and environmentally friendly hierarchical channel construction and high-yield production.

CN122520082BActive Publication Date: 2026-11-06ANQING BEIHUA UNIV SCI & TECH PARK CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611031204.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-11-06
Estimated Expiration
2046-07-13

AI Technical Summary

Technical Problem

Existing technologies require the addition of water when synthesizing hierarchical porous Beta molecular sieves, resulting in large amounts of waste liquid discharge and serious raw material loss. In addition, traditional methods have problems such as high equipment requirements, high energy consumption, and cumbersome processes.

Method used

In an extremely low water volume system without the need for additional water, a hierarchical porous Beta molecular sieve is synthesized by introducing inorganic salts as mesoporous initiators and utilizing the high-viscosity gel during the grinding and mixing process. The anions and cations ionized from the inorganic salts generate mesopores in the molecular sieve lattice.

Benefits of technology

This method enables the synthesis of hierarchical Beta molecular sieves with high mesoporous specific surface area and mesoporous pore volume, reducing the use of organic template agents, simplifying the process, lowering production costs, and improving reactor space utilization and product yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122520082B_ABST
    Figure CN122520082B_ABST
Patent Text Reader

Abstract

The application provides a kind of multi-level hole Beta molecular sieve material and its preparation method, which comprises: grinding and mixing silicon source, aluminum source, organic template agent and inorganic salt, the obtained mixture is directly crystallized, filtered, washed and calcined under the condition that no additional water is added throughout the process, and the multi-level hole Beta molecular sieve material is obtained in one step.The preparation method of the multi-level hole Beta molecular sieve provided by the application introduces inorganic salt in a very low water amount synthesis system without external water, which causes the distortion of the molecular sieve lattice and leads to the formation of framework mesopores, achieving the environmentally friendly synthesis of multi-level hole Beta molecular sieve without post-modification.The obtained multi-level hole Beta molecular sieve has high crystallinity, large mesopore specific surface area and mesopore volume.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of molecular sieve synthesis technology, specifically to a hierarchical porous Beta molecular sieve material and its preparation method. Background Technology

[0002] Developing hierarchical porous Beta molecular sieves is of great significance for improving the catalytic conversion performance of macromolecules. Currently, common strategies for introducing mesopores often involve post-treatment desilication and dealumination, but these methods frequently generate large amounts of acidic or alkaline wastewater and damage the intrinsic acidity and crystal structure of the molecular sieve during treatment. Therefore, methods that directly introduce mesopores during the synthesis of molecular sieves using traditional hydrothermal synthesis systems are widely popular. However, traditional hydrothermal synthesis systems typically require large amounts of water as the reaction medium, leading to losses of raw materials due to dissolution in the mother liquor and large wastewater discharge, which limits the industrial application of this material. Therefore, developing a low-wastewater-discharge synthesis method for hierarchical porous Beta molecular sieves has significant theoretical and practical value.

[0003] Mother liquor recycling is a solution to reduce wastewater discharge and raw material loss during molecular sieve synthesis. Hu et al. (Microporous and Mesoporous Materials, 2019, 283: 110-118.) used a gel-like solid-phase method, with silica-alumina dry gel as the silica-alumina source and potassium hydroxide as the alkali source, to rapidly and efficiently synthesize W molecular sieves within a low water content range of n(H2O) / n(SiO2) = 5.55-14.81. This method significantly reduces water consumption, shortens crystallization time, improves raw material utilization, and simplifies the mother liquor recovery process by constructing a liquid-solid two-phase transformation mechanism. However, the cost of mother liquor recovery using this method remains high.

[0004] Another approach is the dry gel method, which reduces the amount of water used in the crystallization process and minimizes the loss of raw materials in the mother liquor. Xu et al. (Chemical Communications, 1990, (10): 755-756.) first reported a new gas-phase synthesis technique for ZSM-5 molecular sieves. They placed amorphous silica-alumina gel on a porous sieve plate inside a reactor, allowing it to contact only the mixed vapors of ethylenediamine, triethylamine, and water at the bottom of the reactor. Under conditions without direct contact with the liquid phase, ZSM-5 molecular sieves with nano-packed mesopores were successfully synthesized at 453-473 K for 5-7 days. This method eliminates the waste liquid discharge problem in traditional hydrothermal synthesis by constructing a gas-solid phase conversion system, and the mixed solvent at the bottom of the reactor can be recycled, significantly reducing the consumption of organic amines and the synthesis cost. Even in the dry gel state, ZSM-5 can still crystallize through a solid-phase conversion mechanism. However, this method still essentially relies on an organic amine-water vapor atmosphere as the mass transfer medium, making the process cumbersome and the experimental cycle long. The synthesis process still requires the addition of a large amount of water, and drying equipment is also needed to prepare dry gels, which increases the equipment requirements and production energy consumption.

[0005] To address the issue that the vapor-gel method still requires the addition of water during synthesis, Zhang Wei et al. (Petrochemical Technology, 2015, 44(1):47-54) synthesized nanoscale ZSM-5 molecular sieves using coarse-porous silica gel as the silicon source in an extremely concentrated system (n(H2O) / n(SiO2) = 5~12). The molecular sieves exhibit abundant mesopores formed by the aggregation of nanocrystals. This method, by controlling the synthesis parameters under low water-to-solid ratio conditions, achieved the controllable preparation of nanoscale ZSM-5 molecular sieves, reduced the mother liquor discharge, and improved the molecular sieve yield. However, the successful implementation of this method mainly targets nanoscale ZSM-5 molecular sieves with two-dimensional channel MFI topology.

[0006] The method for synthesizing high-silica Y molecular sieves by dry gel conversion disclosed by Wang Linying et al. (Chinese patent application CN201910312322.2) achieves the synthesis of high-silica FAU structure molecular sieves under ultra-low water conditions, but its system still depends on the presence of a certain amount of added water. The product has only a single microporous structure and does not involve the in-situ construction of multi-level channels. Moreover, the synthesis object is limited to Y molecular sieves and it is difficult to extend to the more complex Beta molecular sieve system.

[0007] Regarding the synthesis of hierarchical porous molecular sieves, Yi et al. (Journal of Catalysis, 2019, 380: 204-214.) synthesized hierarchical porous Beta molecular sieves via a two-step method involving nitric acid dealumination and high-temperature calcination. This method progressively removed framework aluminum atoms and reconstructed silanol nests through condensation, thereby constructing a rich mesoporous structure. The specific surface area of ​​the product (BET) remained between 380 and 440 m². 2Between / g. After removing the framework aluminum, high-temperature calcination promotes the condensation and reconstruction of silanol nests, improves structural stability, and avoids the framework collapse problem caused by the introduction of mesopores.

[0008] Wang et al. (Catalysis Letters, 2023, 153(12):3837-3845.) synthesized hierarchical beta molecular sieves using the template effect of the soft template agent polydiallyldimethylammonium chloride (PDDA), and achieved precise control of mesopore size by adjusting the molecular weight of PDDA. However, the use of organic mesoporous template agents limits the industrial application of this method.

[0009] Therefore, although a great deal of research has been done on the synthesis of hierarchical porous molecular sieves, the synthesis of Beta molecular sieves with mesoporous-microporous composite channels using inorganic mesoporous initiators under extremely low water conditions without the need for additional water remains a huge challenge. Summary of the Invention

[0010] To address the aforementioned technical problems, this invention achieves the synthesis of hierarchical Beta molecular sieves by crystallizing in an extremely low water volume system without the need for additional water addition, and by introducing inorganic salts as mesoporous initiators into the synthesis system. This technique differs significantly from conventional hydrothermal synthesis systems, characterized by the ability to synthesize highly crystalline molecular sieves without the need for additional water. Furthermore, the extremely high gel viscosity during grinding and mixing under extremely low water volume conditions prevents the ionized anions and cations from the inorganic salts from being uniformly dispersed in the solvent as in conventional hydrothermal systems, leading to lattice distortion of the molecular sieve and the formation of intracrystalline mesopores.

[0011] This invention achieves the environmentally friendly synthesis of hierarchical Beta molecular sieves with high mesoporous specific surface area and mesoporous pore volume by introducing inorganic salts into a system without the need for external water addition; in addition, this method significantly shortens the crystallization time of the molecular sieve.

[0012] To achieve the above objectives, the present invention provides a method for preparing a hierarchical porous Beta molecular sieve, wherein the preparation method includes the following steps: (1) The silicon source, seed crystals and organic microporous template agent are ground and mixed to obtain silicon source gel; (2) Add aluminum source grinding solid to the silicon source gel obtained in (1) and mix it evenly to obtain a high viscosity metal aluminosilicate gel. Add inorganic salt compound and continue grinding to disperse it evenly. Transfer the ground gel to a polytetrafluoroethylene liner, then put it into a reaction vessel, and finally place it in the reactor to crystallize for a certain period of time. Cool the reaction product to room temperature, filter, wash, dry, and calcine to obtain the product; The molar ratio of silicon, aluminum, and sodium in the metal aluminosilicate gel, calculated as SiO2, Al2O3, and Na2O, is 1:(0.012-0.02):(0.12-0.2). The content of the inorganic salt and the molar ratio of silicon in the metal aluminosilicate gel, L / SiO2, are L / 0.09-0.2, where L represents the inorganic salt compound. The molar ratio of the content of the microporous template agent to the silicon element in the metal aluminosilicate gel, M / SiO2, is 0.1-0.2, where M represents the microporous template agent. The content of the seed crystals is in the mass ratio of silicon in the metal aluminosilicate gel, N / SiO2 = 0.05-0.2, where N represents the Beta molecular sieve seed crystals.

[0013] According to a specific embodiment of the present invention, preferably, the inorganic salt compound includes one or more of sodium carbonate, potassium carbonate, sodium bicarbonate, calcium carbonate, potassium sulfate, sodium sulfate, sodium chloride, and potassium chloride.

[0014] According to a specific embodiment of the present invention, preferably, the crystallization temperature is 130-170℃, the crystallization time is 9-20h, and the calcination temperature is 400-600℃ for 4-8h.

[0015] According to a specific embodiment of the present invention, preferably, the silicon source includes one or more of the following: silica sol and water glass.

[0016] According to a specific embodiment of the present invention, preferably, the aluminum source includes one or more of the following: sodium aluminate, aluminum oxide, aluminum sulfate, aluminum isopropoxide, boehmite, aluminum chloride, aluminum citrate, aluminum hydroxide, and aluminum nitrate.

[0017] According to a specific embodiment of the present invention, preferably, the microporous template agent comprises one or more of tetraethylammonium hydroxide, tetraethylammonium bromide, triethylamine, and tetramethylammonium hydroxide.

[0018] The present invention also provides a hierarchical porous Beta molecular sieve, which is obtained by the above preparation method.

[0019] According to a specific embodiment of the present invention, preferably, the total specific surface area of ​​the hierarchical porous Beta molecular sieve is 450-600 m². 2 ·g -1 The mesoporous specific surface area is 65-160 m². 2 ·g -1 The mesopore volume is 0.1-0.2 cm³. 3 ·g -1 .

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The method for preparing multi-level porous Beta molecular sieve material provided by the present invention uses seed crystals as guides and inorganic salts as mesoporous initiators, which greatly reduces the consumption of organic template agents and post-processing steps, and synthesizes the target material in an environmentally friendly, simple and efficient manner.

[0021] (2) The method for preparing multi-level porous Beta molecular sieve material provided by the present invention achieves in-situ construction of multi-level channels within the crystal in an environmentally friendly and economical manner under extremely low water conditions without the need for additional water addition. Furthermore, under extremely low water conditions, the reaction system volume is small, which can effectively improve the space utilization rate of the reaction vessel.

[0022] (3) The multi-level porous Beta molecular sieve material provided by the present invention can maintain a high degree of crystallinity and has a large mesoporous specific surface area and mesoporous introduction amount. Attached Figure Description

[0023] Figure 1 The XRD patterns are of the multi-level porous Beta molecular sieves prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 3, Example 6, and Example 8.

[0024] Figure 2 Nitrogen adsorption-desorption isotherms of the hierarchical porous Beta molecular sieves prepared in Comparative Examples 1, 2, 3, 1, 8, and 12.

[0025] Figure 3 The pore size distribution diagrams are for the multi-level porous Beta molecular sieves prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 8, and Example 12.

[0026] Figure 4 The image shows a transmission electron microscope (TEM) image of the hierarchical porous Beta molecular sieve prepared in Example 1. Detailed Implementation

[0027] The experimental materials used in the following examples were sourced from the following sources: the main components of the water glass in the silicon source were 27.8 wt% SiO2, 63.2 wt% H2O, and 8.98 wt% Na2O; the main components of the silica sol were 30.0 wt% SiO2, 69.5 wt% H2O, and 0.5 wt% Na2O; the aluminum sources (sodium aluminate, alumina, aluminum sulfate, aluminum isopropoxide, boehmite, aluminum chloride, aluminum citrate, aluminum hydroxide, and aluminum nitrate) were all commercially available analytical grade reagents from Xilong Scientific Co., Ltd.; the inorganic salt compounds (sodium carbonate, potassium carbonate, sodium bicarbonate, calcium carbonate, potassium sulfate, sodium sulfate, sodium chloride, and potassium chloride) were all from Shanghai Maclean Biochemical Technology Co., Ltd.; the microporous template agents (tetraethylammonium hydroxide, tetraethylammonium bromide, triethylamine, and tetramethylammonium hydroxide) were all from Shanghai Maclean Biochemical Technology Co., Ltd.; and the seed crystals, calculated as SiO2 and Al2O3 with a molar ratio of 30, were from Tianjin Nanhua Catalyst Co., Ltd. Other test materials and reagents, unless otherwise specified, can be obtained commercially.

[0028] The molecular sieves provided in the examples and comparative examples were tested using the following analytical instruments: 1. Phase analysis and confirmation were performed using a Shimadzu XRD-7000 X-ray crystal powder diffractometer. Instrument parameters: Cu-Ka rays, wavelength 0.1543 nm, tube voltage 40 kV, tube current 30 mA. Sample testing conditions: scanning angle 5°-40°, scanning speed 8° / min.

[0029] 2. The adsorption-desorption isotherms of the samples were determined at liquid nitrogen temperature using an ASAP2020M fully automated adsorption instrument manufactured by Micromeritics, USA. Nitrogen gas was used as the adsorbate. The T-plot model was used to distinguish the internal and external surface areas of the samples. The pore volume and pore size distribution were determined by the static volumetric method, thereby calculating the pore structure parameters.

[0030] 3. To visually observe the morphology of the composite material, a Hitachi HT7700 transmission electron microscope was used for sample characterization. The operating voltage of the instrument was 120kV. The sample preparation process was as follows: the sample to be tested was first ground into a fine powder and dispersed in an ethanol solution. After ultrasonic treatment for 20 minutes, an appropriate amount of suspension was dropped onto a copper mesh support coated with a carbon film. After the solvent evaporated, the microstructure was observed.

[0031] The following are the specific implementation methods. Example 1: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. The initial gel ratio is 0.16Na₂O:SiO₂:0.017Al₂O₃:0.16TEAOH:0.12K₂CO₃, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.07. The specific steps are as follows: (1) Weigh 32.45g of water glass and place it in a mortar. Add 8.62g of silicon powder and mix. Then add 27.69g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 1.22g of seed crystal to obtain silicon source gel.

[0032] (2) First, weigh 4.8g of potassium carbonate and add it to the mortar, grind it evenly, then weigh 3.3g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0033] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 150°C for 12 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 5 hours to obtain the product.

[0034] Example 2: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. The initial gel ratio is 0.12Na₂O:SiO₂:0.012Al₂O₃:0.10TEAOH:0.09Na₂CO₃, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.05. The specific steps are as follows: (1) Weigh 24.33g of water glass (SiO2 content 27.8wt%, Na2O content 8.98wt%) and place it in a mortar. Add 10.88g of silicon powder and then add 17.30g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 0.88g of seed crystal to obtain silicon source gel.

[0035] (2) First, weigh 2.80g of sodium carbonate and add it to the mortar, grind it evenly, then weigh 2.35g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0036] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 145°C for 10 h. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 550°C for 5.5 h to obtain the product.

[0037] Example 3: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. The initial gel ratio is 0.20Na₂O:SiO₂:0.02Al₂O₃:0.20TEAOH:0.20NaHCO₃, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.2. The specific steps are as follows: (1) Weigh 40.55g of water glass and place it in a mortar. Add 6.37g of silicon powder and then add 34.60g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 3.53g of seed crystals to obtain silicon source gel.

[0038] (2) First, weigh 4.93g of sodium bicarbonate and add it to the mortar, grind it evenly, then weigh 3.91g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0039] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 160°C for 11 h. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 600°C for 4 h to obtain the product.

[0040] Example 4: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. The initial gel ratio is 0.12Na₂O:SiO₂:0.02Al₂O₃:0.16TEAOH:0.12CaCO₃, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.07. The specific steps are as follows: (1) Weigh 24.33g of water glass and place it in a mortar. Add 10.88g of silicon powder and then add 27.68g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 1.23g of seed crystal to obtain silicon source gel.

[0041] (2) First, weigh 3.52g of calcium carbonate and add it to the mortar, grind it evenly, then weigh 3.91g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0042] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 170°C for 9 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 530°C for 4.5 hours to obtain the product.

[0043] Example 5: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. An initial gel ratio of 0.20 Na₂O:SiO₂:0.012 Al₂O₃:0.16 TEAOH:0.12 K₂SO₄ was used, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.07. The specific steps are as follows: (1) Weigh 40.55g of water glass and place it in a mortar. Add 6.37g of silicon powder and then add 27.68g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 1.23g of seed crystal to obtain silicon source gel.

[0044] (2) First, weigh 6.13g of potassium sulfate and add it to the mortar, grind it evenly, then weigh 2.35g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0045] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 165°C for 11 h. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 480°C for 6 h to obtain the product.

[0046] Example 6: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. An initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.10TEAOH:0.09Na₂SO₄ was used, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.05. The specific steps are as follows: (1) Weigh 32.44g of water glass and place it in a mortar. Add 8.62g of silicon powder and then add 17.30g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 0.88g of seed crystals to obtain silicon source gel.

[0047] (2) First, weigh 3.75g of sodium sulfate and add it to the mortar, grind it evenly, then weigh 3.33g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0048] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 130°C for 14 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 600°C for 4 hours to obtain the product.

[0049] Example 7: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. An initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.20TEAOH:0.20NaCl was used, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.2. The specific steps are as follows: (1) Weigh 32.44g of water glass and place it in a mortar. Add 8.62g of silicon powder and then add 34.60g of TEAOH aqueous solution (mass fraction 25%). Mix well and then add 3.53g of seed crystals to obtain silicon source gel.

[0050] (2) First, weigh 3.43g of sodium chloride and add it to the mortar, grind it evenly, then weigh 3.33g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0051] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 165°C for 13 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 5 hours to obtain the product.

[0052] Example 8: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. An initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.16TEAOH:0.12KCl was used, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.07. The specific steps are as follows: (1) Weigh 32.44g of water glass and place it in a mortar. Add 8.62g of silicon powder and then add 27.68g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 1.23g of seed crystal to obtain silicon source gel.

[0053] (2) First, weigh 2.63g of potassium chloride and add it to the mortar, grind it evenly, then weigh 3.33g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0054] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 150°C for 12 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 5 hours to obtain the product.

[0055] Example 9: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. The initial gel ratio is 0.16Na₂O:SiO₂:0.017Al₂O₃:0.16TEAOH:0.09K₂CO₃, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.07. The specific steps are as follows: (1) Weigh 32.45g of water glass and place it in a mortar. Add 8.62g of silicon powder and mix. Then add 27.69g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 1.22g of seed crystal to obtain silicon source gel.

[0056] (2) First, weigh 3.6g of potassium carbonate and add it to the mortar, grind it evenly, then weigh 3.3g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0057] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 150°C for 12 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 5 hours to obtain the product.

[0058] Example 10: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. An initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.16TEAOH:0.2K₂CO₃ was used, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.07. The specific steps are as follows: (1) Weigh 32.45g of water glass and place it in a mortar. Add 8.62g of silicon powder and mix. Then add 27.69g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 1.22g of seed crystal to obtain silicon source gel.

[0059] (2) First, weigh 8g of potassium carbonate and add it to the mortar, grind it evenly, then weigh 3.3g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0060] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 150°C for 12 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 5 hours to obtain the product.

[0061] Example 11: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. An initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.16TEAOH:0.12K₂CO₃ was used, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.05. The specific steps are as follows: (1) Weigh 32.45g of water glass and place it in a mortar. Add 8.62g of silicon powder and mix. Then add 27.69g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 0.87g of seed crystals to obtain silicon source gel.

[0062] (2) First, weigh 4.8g of potassium carbonate and add it to the mortar, grind it evenly, then weigh 3.3g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0063] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 150°C for 12 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 5 hours to obtain the product.

[0064] Example 12: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. An initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.16TEAOH:0.12K₂CO₃ was used, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.2. The specific steps are as follows: (1) Weigh 32.45g of water glass and place it in a mortar. Add 8.62g of silicon powder and mix. Then add 27.69g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 3.48g of seed crystals to obtain silicon source gel.

[0065] (2) First, weigh 4.8g of potassium carbonate and add it to the mortar, grind it evenly, then weigh 3.3g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0066] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 150°C for 12 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 5 hours to obtain the product.

[0067] Example 13: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. An initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.1TEAOH:0.12K₂CO₃ was used, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.07. The specific steps are as follows: (1) Weigh 32.45g of water glass and place it in a mortar. Add 8.62g of silicon powder and mix. Then add 17.31g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 1.22g of seed crystal to obtain silicon source gel.

[0068] (2) First, weigh 4.8g of potassium carbonate and add it to the mortar, grind it evenly, then weigh 3.3g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0069] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 150°C for 12 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 5 hours to obtain the product.

[0070] Example 14: This example provides a method for preparing a hierarchical porous Beta molecular sieve material. An initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.2TEAOH:0.12K₂CO₃ was used, with seed crystals added at a ratio of m(seeds) / m(SiO₂) = 0.07. The specific steps are as follows: (1) Weigh 32.45g of water glass and place it in a mortar. Add 8.62g of silicon powder and mix. Then add 34.61g of TEAOH aqueous solution (mass fraction 25%). After mixing evenly, add 1.22g of seed crystal to obtain silicon source gel.

[0071] (2) First, weigh 4.8g of potassium carbonate and add it to the mortar, grind it evenly, then weigh 3.3g of Al2(SO4)3·18H2O solid and put it into the mortar, grind the solid with a pestle to make it evenly dispersed.

[0072] (3) The ground high-viscosity gel was transferred to a polytetrafluoroethylene liner, then placed in a reaction vessel and locked, and finally placed in a reactor to crystallize at 150°C for 12 hours. The reaction product was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 5 hours to obtain the product.

[0073] Comparative Example 1: This comparative example provides a conventional hydrothermal synthesis method. Except for the addition of extra water, the feed ratio is the same as in Example 1, with an initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.16TEAOH:0.12K₂CO₃:15H₂O. Seed crystals are added at a ratio of m(seeds) / m(SiO₂) = 0.07. A hierarchical porous Beta molecular sieve is prepared using the following steps: (1) Weigh 18.65g of TEAOH aqueous solution (25% by mass) and 21.86g of water glass in a clean beaker, then add 5.80g of silicon powder and 11.05g of deionized water. After mixing evenly, add 0.83g of seed crystals to obtain silicon source gel.

[0074] (2) Preparation of aluminum source: Take 14g of deionized water into a clean beaker, add 2.22g of Al2(SO4)3·18H2O into the beaker and stir until completely dissolved to obtain aluminum source solution.

[0075] (3) Mix silicon source and aluminum source to obtain initial gel, add 3.31g potassium carbonate, age at 40℃ for 4h, transfer to inner liner, load into reaction vessel and crystallize at 150℃ for 24h in oven.

[0076] (4) After cooling, vacuum filtration and constant temperature drying are performed in sequence, followed by calcination at 500℃ for 5 hours to finally obtain the target product.

[0077] Comparative Example 2: This comparative example uses the dry gel conversion method for synthesis. Except for the addition of extra water and the absence of a mesoporous initiator, the feed ratio is the same as in Example 1, with an initial gel ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.16TEAOH:15H₂O. Seed crystals were added at a ratio of m(seeds) / m(SiO₂) = 0.07. Hierarchical porous Beta molecular sieves were prepared using the following steps: 1. Preparation of precursor gel (1) Weigh 18.65g of TEAOH aqueous solution (25% by mass) and 21.86g of water glass in a clean beaker, then add 5.80g of silicon powder and 11.05g of deionized water. After mixing evenly, add 0.83g of seed crystals to obtain silicon source gel.

[0078] (2) Preparation of aluminum source: Take 14g of deionized water into a clean beaker, add 2.22g of Al2(SO4)3·18H2O into the beaker and stir until completely dissolved to obtain aluminum source solution.

[0079] (3) Mix the silicon source and aluminum source and stir at room temperature for 2 hours to obtain the initial gel.

[0080] 2. Dry gel molding The above precursor gel was placed in a 60°C oven and heated for 12 hours to remove moisture and form a dry gel for later use.

[0081] 3. Steam-assisted crystallization (1) Weigh 5.0g of dry gel, coarsely crush it and transfer it to a 40mL polytetrafluoroethylene cup. Place the polytetrafluoroethylene cup into a 180mL stainless steel high-pressure reactor lined with polytetrafluoroethylene and add 1.0g of distilled water to the bottom of the reactor.

[0082] (2) Seal the reactor and place it in a preheated oven for static crystallization at 150°C for 48 hours.

[0083] (3) After crystallization, cool to room temperature, collect the solid product, wash with distilled water, dry and calcine at 500℃ for 5h to obtain the target product; Comparative Example 3: Except for the addition of extra water and the absence of a mesoporous initiator, the feed ratio in this comparative example was the same as in Example 1, with an initial gelation ratio of 0.16Na₂O:SiO₂:0.017Al₂O₃:0.16TEAOH:15H₂O. Seed crystals were added at a ratio of m(seeds) / m(SiO₂) = 0.07. A hierarchical porous Beta molecular sieve was prepared using the following steps: (1) Weigh 18.65g of TEAOH aqueous solution (25% by mass) and 21.86g of water glass in a clean beaker, then add 5.80g of silicon powder and 11.05g of deionized water. After mixing evenly, add 0.83g of seed crystals to obtain silicon source gel.

[0084] (2) Preparation of aluminum source: Take 14g of deionized water into a clean beaker, add 2.22g of Al2(SO4)3·18H2O into the beaker and stir until completely dissolved to obtain aluminum source solution.

[0085] (3) Mix silicon source and aluminum source to prepare initial gel. After aging at 40°C for 4 hours, transfer to inner liner, load into reaction vessel and crystallize at 150°C for 24 hours in oven.

[0086] (4) After cooling, vacuum filtration and constant temperature drying are performed in sequence, followed by calcination at 500℃ for 5 hours to finally obtain the target product.

[0087] The pore structure parameters of the hierarchical porous Beta molecular sieve materials prepared in Examples 1 to 14 and Comparative Examples 1 to 3 are compared with those of conventional Beta molecular sieves. The results are shown in Table 1. Here, relative crystallinity represents the relative crystallinity of the Beta molecular sieve material, S... total S represents the total specific surface area. ext S represents the specific surface area of ​​mesopores. mic V represents the specific surface area of ​​micropores.meso D represents the volume of mesopores. ave The average pore size is represented in Table 2. Table 2 shows the material parameters used in the synthesis of Beta molecular sieve materials.

[0088] Table 1. Pore structure parameters of samples from Examples 1 to 14 and Comparative Examples 1 to 3.

[0089] As shown in Table 2, none of the embodiments of this invention require the addition of any additional water during the synthesis process. In contrast, the conventional hydrothermal synthesis method requires 2.99g of water (Comparative Example 1) and 2.98g of water (Comparative Example 3) to produce 1g of zeolite, while the dry gel conversion method (Comparative Example 2) requires an even higher amount of water (3.68g). By completely eliminating the need for added water in the solid-phase grinding-crystallization process, the problem of excessive waste liquid is eliminated at the source. Simultaneously, the low-water system avoids the loss of raw materials dissolved in the mother liquor, resulting in a significantly higher product yield than the hydrothermal method (10.84g in Example 1 and only 8.38g in Comparative Example 1). Furthermore, the addition of inorganic salts promotes solid-phase mass transfer, shortening the crystallization time from 24h in Comparative Example 1 to 12h in Example 1. Therefore, this invention not only synthesizes a hierarchical porous Beta molecular sieve with high crystallinity and a large mesoporous specific surface area but also establishes a novel environmentally friendly synthetic route.

[0090] According to the data in Table 1, the mesoporous specific surface area of ​​the hierarchical Beta molecular sieve material provided in Example 1 is 144 m². 2 ·g -1 The mesopore volume is 0.16 cm³. 3 ·g -1 The average pore size is 2.6 nm, while the mesoporous specific surface area of ​​conventional Beta molecular sieves (Comparative Example 3) is 70 m². 2 ·g -1 The hydrothermally synthesized sample (Comparative Example 1) was 95m. 2 ·g -1 The hydrothermally synthesized sample (Comparative Example 1) showed an increase in mesopore size compared to the conventional Beta molecular sieve (Comparative Example 3), but this increase was far less than that of Example 1. This demonstrates that a synthesis system with extremely low water content can effectively increase the mesopore specific surface area and pore volume of the product molecular sieve.

[0091] Compared with the dry gel conversion method (Comparative Example 2), Example 1 showed a significant improvement in both crystallinity and mesoporous specific surface area. This result indicates that the introduction of inorganic salts in the extremely low water content synthesis system of this invention is crucial for the introduction of mesopores.

[0092] Figure 1 The images show the XRD patterns of the Beta molecular sieve materials prepared in Comparative Examples 1, 2, 1, 3, 6, and 8. Figure 1As can be seen, compared with Comparative Example 1, the hierarchical porous Beta molecular sieves provided in Examples 1, 3, 6, and 8 are typical Beta molecular sieves. Furthermore, as shown in Table 1, the relative crystallinity of the molecular sieves in Examples 1, 8, etc., remains at a high level overall, indicating that the appropriate introduction of inorganic salts in the extremely low water content synthesis system can contribute to seed crystal formation and TEA production. + Its guiding role in the system ultimately leads to more complete crystallization.

[0093] Figure 2 This is the N2 adsorption-desorption isotherm of the hierarchical porous Beta molecular sieves prepared in Comparative Examples 1, 2, 3, 1, 8, and 12 of this invention. Figure 2 As can be seen from the N2 adsorption-desorption isotherms, the adsorption-desorption isotherms of the hierarchical porous Beta molecular sieves provided in Examples 1, 8, and 12 are mixed type I and type IV adsorption-desorption curves with H4 type hysteresis loops, which have obvious characteristics of mesoporous materials. This verifies that the present invention has successfully prepared a Beta molecular sieve material with hierarchical pores.

[0094] Table 2. Material addition amounts for Examples 1 to 14 and Comparative Examples 1 to 3

[0095] Furthermore, as can be seen from the data in Table 2, Example 1 only requires crystallization for 12 hours. This is because the addition of inorganic salts can hinder the formation of the gel network, reduce the degree of condensation of the silica-alumina gel, fragment the silica-alumina gel, enhance the mass transfer of the molecular sieve raw material silica-alumina gel, and change the crystallization process from rearrangement to raw material attachment and growth, thereby accelerating the crystallization rate.

[0096] Figure 3 This is a pore size distribution diagram of the hierarchical porous Beta molecular sieves prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 8, and Example 12 of this invention. Figure 3 As can be seen from the pore size distribution curve, the multi-level porous Beta molecular sieves provided in Examples 1, 8, and 12 have obvious mesopore distribution in the range of 2-10 nm.

[0097] Figure 4 The images show transmission electron microscopy (TEM) images of the sample from Embodiment 1 of the present invention and the hierarchical porous Beta molecular sieve. A clear mesoporous distribution can be observed in the images, indicating that the present invention has successfully introduced a clear mesoporous structure into the Beta molecular sieve framework.

Claims

1. A method for preparing a hierarchical porous Beta molecular sieve material, characterized in that, in, The preparation method includes the following steps: (1) The silicon source, seed crystals and organic microporous template agent are ground and mixed to obtain silicon source gel; (2) Add aluminum source solid to the silicon source gel obtained in (1) and grind it to make it evenly mixed to obtain high viscosity metal aluminosilicate gel. Add inorganic salt compound and continue grinding to make it evenly dispersed. Transfer the ground gel to a polytetrafluoroethylene liner and then put it into a reaction vessel. Finally, place it in the reactor to crystallize for a certain time. Cool the reaction product to room temperature, filter, wash, dry and calcine to obtain the product. The molar ratio of silicon, aluminum, and sodium in the metal aluminosilicate gel, calculated as SiO2, Al2O3, and Na2O, is 1:(0.012-0.02):(0.12-0.2). The content of the inorganic salt compound and the molar ratio of silicon in the metal aluminosilicate gel, L / SiO2, are L=0.09-0.2, where L represents the inorganic salt compound. The molar ratio of the content of the microporous template agent to the silicon element in the metal aluminosilicate gel, M / SiO2, is 0.1-0.2, where M represents the microporous template agent. The content of the seed crystals is in the mass ratio of silicon in the metal aluminosilicate gel, N / SiO2 = 0.05-0.2, where N represents the Beta molecular sieve seed crystals; The silicon source includes one or more of the following: silica sol and water glass; The inorganic salt compound includes one or more of sodium carbonate, potassium carbonate, sodium bicarbonate, calcium carbonate, potassium sulfate, sodium sulfate, sodium chloride, and potassium chloride. The microporous template agent includes: tetraethylammonium hydroxide and / or tetramethylammonium hydroxide; The crystallization temperature is 130-170℃, the crystallization time is 9-20h, and the calcination temperature is 400-600℃ for 4-8h.

2. The method for preparing a hierarchical porous Beta molecular sieve material according to claim 1, characterized in that, in, The aluminum source includes one or more of the following: sodium aluminate, aluminum oxide, aluminum sulfate, aluminum isopropoxide, boehmite, aluminum chloride, aluminum citrate, aluminum hydroxide, and aluminum nitrate.

3. A hierarchical porous Beta molecular sieve material, obtained by the preparation method of the hierarchical porous Beta molecular sieve material according to claim 1 or 2, characterized in that, The total specific surface area of ​​the hierarchical porous Beta molecular sieve is 450-600 m². 2 ·g -1 The mesoporous specific surface area is 65-160 m². 2 ·g -1 The mesopore volume is 0.1-0.2 cm³. 3 ·g -1 .

Citation Information

Patent Citations

  • A method for the dry gel conversion synthesis of high-silica Y molecular sieves

    CN111825102B

  • Method for synthesizing B body-enriched Beta zeolite molecular sieve by fluoride-free solvent-free route

    CN106517233A

  • Beta molecular sieve with intracrystalline mesopores and preparation method thereof

    CN121627012A